How do laws and institutions affect recovery rates on collateral? - Hans Degryse; Vasso Ioannidou; José María Liberti; Jason Sturgess (Queen Mary University of London, School of Economics and Finance, 2018)
We show that laws and institutions that grant creditors stronger enforcement rights and bargaining power upon default increase expected recovery rates on collateral. Using unique data that provides ex-ante appraised liquidation values on secured loans for a single global bank, we estimate within-borrower effects of enforcement law on expected recovery rates. We show that movable collateral, which is less redeployable, susceptible to agency problems, and faster to depreciate, exhibits lower expected recovery rates that are more vulnerable to enforcement. Further, the bank compensates for lower expected recovery rates through higher interest rates. The results highlight that a lender's expected recovery rate is a firststage mechanism through which stronger enforcement law affects loan-to-value ratios, lending decisions, and real outcomes.
Keywords: K4; G2; G33; 330